Deep diving towards a vison for social justice: a visual dream matrix - Hayley Berman; Neo Pule (South African Journal of Arts Therapies)
This article explores the utilization of Social Dreaming as a methodology to engage conference participants at the University of Johannesburg in understanding the interplay between individual and group psyche. Through group analytic techniques, participants shared nighttime dreams and free associations related to the conference theme of social justice, creating a collaborative space for reflection and new knowledge generation. The structured process, reminiscent of community gatherings, facilitated creative expression and collective resonance, fostering a democratic approach to learning and teaching. Themes such as trauma, repression, and societal injustices emerged, providing insight into both personal and collective experiences. The article highlights the transformative potential of Social Dreaming in eliciting deep reflection and societal awareness.